Circulating neurotrophins and hemostatic risk factors of atherothrombotic cardiovascular disease at baseline and during sympathetic challenge: the SABPA study - Roland von Känel (Nature Portfolio, 2021)
Abstract Sympathetic activation may trigger acute coronary syndromes. We examined the relation between circulating neurotrophic factors and hemostatic risk factors of atherothrombotic cardiovascular disease at baseline and in response to acute mental stress to establish a brain–heart link. In 409 black and white South Africans, brain-derived neurotrophic factor (BDNF) and fibrinolytic measures were assessed at baseline. Glial cell-derived neurotrophic factor (GDNF), S100 calcium-binding protein (S100B), von Willebrand factor (VWF), fibrinogen and D-dimer were assessed at baseline and 10 min after the Stroop test. Neurotrophins were regressed on hemostatic measures adjusting for demographics, comorbidities, cardiometabolic factors and health behaviors. Higher baseline BDNF was associated with greater stress-induced increase in fibrinogen (p = 0.003) and lower D-dimer increase (p = 0.016). Higher baseline S100B was significantly associated with higher baseline VWF (p = 0.031) and lower fibrinogen increase (p = 0.048). Lower baseline GDNF was associated with higher baseline VWF (p = 0.035) but lower VWF increase (p = 0.001). Greater GDNF (p = 0.006) and S100B (p = 0.042) increases were associated with lower VWF increase. All associations showed small-to-moderate effect sizes. Neurotrophins and fibrinolytic factors showed no significant associations. The findings support the existence of a peripheral neurothrophin-hemostasis interaction of small-to-moderate clinical relevance. The implications for atherothrombotic cardiovascular disease need further exploration.